Prevalence and risk factors to Leptospira sp. Infection in dogs attended at veterinary clinics in João Pessoa, Paraíba State, Northeastern brazil - Brasil, A. W. L.; Costa, D. F. C.; Pimenta, C. L. M. R.; Parentoni, R. N.; Alves, C. J.; Santos, C. S. A. B.; Azevedo, S. S. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
From the one health point of view canine leptospirosis is a disease of great relevance since dogs are sources of infection of leptospires to human beings.